Pengaruh Yoga Pranayama terhadap Kualitas Hidup Penderita PPOK di Rumah Sakit Sanjiwani Gianyar - Ni Kadek Yuni Lestari; Ni Luh Gede Intan Saraswati (Malahayati Nursing Journal, 2022)
ABSTRACT COPD is one of the leading causes of death in addition to coronary heart disease, cerebrovascular disease and acute respiratory infections and is the third leading cause of death worldwide. The pathological impact caused is an increase in functional residual capacity, a decrease in arterial blood supply to the systemic circulation in the form of a decrease in oxygen saturation, shortness of breath, limited exercise capacity, decreased ability to perform daily activities, loss of productivity and decreased quality of life. The purpose of this study is to analyze the effect of pranayama yoga breathing exercises to the quality of life on the patients with COPD. This study uses the One Group Pre-Test-Posttest Design method. The sampling technique used is non-probability sampling with purposive sampling so that the number of respondents is 20 people. Yoga Pranayama is given 12 times with a duration of 15 minutes every day for 2 weeks.The results showed that the quality of life before being given pranayama yoga intervention was mostly low about 11 respondents (55%) and after the intervention, 10 respondents (50%) had moderate quality of life. The p-value is 0.000 (0.05), which means that there is a significant effect of giving pranayama yoga on the quality of life on the patients with COPD. Pranayama yoga breathing exercises can increase the positive influence in the mind to trigger a sense of relaxation, thereby influencing the sympathetic and parasympathetic nervous systems to send a sense of relaxation throughout the body through the endocrine glands, reducing symptoms of shortness of breath so that respondents can perform their daily activities better. This leads to an increase the quality of life on the patients with COPD. Keywords: Yoga Pranayama, Quality of Life, COPD  ABSTRAK PPOK merupakan salah satu penyebab kematian selain penyakit jantung koroner, penyakit serebrovaskuler dan infeksi akut saluran pernafasan dan menjadi penyebab ke-3 kematian diseluruh dunia. Dampak patologis yang ditimbulkan berupa peningkatan kapasitas residu fungsional, penurunan penyaluran darah arteri ke sirkulasi sistemik berupa penurunan saturasi oksigen, sesak napas, keterbatasan kapasitas latihan, menurunkan kemampuan melakukan aktivitas sehari-hari, hilangnya produktivitas dan menurunnya kualitas hidup.Tujuan penelitian ini adalah untuk menganalisis pengaruh pemberian latihan pernafasan yoga pranayama terhadap kualitas hidup pada pasien PPOK. Penelitian ini menggunakan metode One Group Pre-Test-Posttest Design. Teknik sampling yang digunakan adalah non-probability sampling dengan purposive sampling sehingga didapatkan jumlah responden sebanyak 20 orang. Yoga Pranayama diberikan sebanyak 12 kali dengan durasi 15 menit setiap hari selama 2 minggu. Hasil penelitian menunjukkan kualitas hidup sebelum diberikan intervensi yoga pranayama mayoritas kualitas hidup rendah sebanyak 11 responden (55%) dan setelah intervensi sebanyak 10 responden (50%) memiliki kualitas hidup sedang. Nilai p-value sebesar 0,000 ( 0,05) yang berarti ada pengaruh significant pemberian yoga pranayama terhadap kualitas hidup pada pasien PPOK. Latihan pernafasan yoga pranayama dapat meningkatkan pengaruh positif dalam pikiran untuk memicu rasa rileks, sehingga mempengaruhi sistem saraf simpatik dan parasimpatik untuk mengirimkan rasa rileks ke seluruh tubuh melalui kelenjar endokrin, menurunkan gejala sesak sehingga responden bisa melakukan kegiatan sehari-hari dengan lebih baik. Hal tersebut menyebabkan peningkatan kualitas hidup pasien. Kata Kunci: Yoga Pranayama, Kualitas Hidup, PPOK